Echocardiographic Evaluation of Pulmonary Pressures and Right Ventricular Function after Pediatric Cardiac Surgery: A Simple Approach for the Intensivist - Beghetti, Maurice (Frontiers in Pediatrics, 2017)
Pulmonary hypertension (PH) is diagnosed using cardiac catheterization and is defined as an elevation of mean pulmonary artery pressure (PAP) greater than 25 mmHg. Although invasive hemodynamics remains the gold standard and is mandatory for disease confirmation, transthoracic echocardiography (TTE) is an extremely useful non-invasive and widely available tool that allows for screening and follow-up, in particular, in the acute setting. TTE may be a valuable alternative, allowing for direct measurement and/or indirect assessment of PAP. Because of the complex geometric shape and pattern of contraction of the right ventricle (RV), as well as the inherent complexity of cardiac repair, no single view or measurement can provide definite information on RV function and PAP and/or pulmonary vascular resistance. In addition, specific training and expertise may be necessary to obtain the views and measurements required. Some simple measurements may be of help when rapid evaluation is mandatory and potentially life saving: the assessment of tricuspid and/or pulmonary valve regurgitant jet and the use of the Bernoulli equation allow for measurement of PAP. Measurements such as the analysis of the pulmonary Doppler wave flow, the septal curvature, or the eccentricity index, assessing ventricular interdependence, are useful for indirect assessment. A four-chamber view of the RV gives information on its size, hypertrophy, function (fractional area change), and tricuspid annular plane systolic excursion as an evaluation of the longitudinal function. Based on these simple measurements, TTE can provide detection of PH, measurement or estimation of PAP, and assessment of cardiac function. TTE is also of importance in follow up of PH as well as providing an assessment of therapeutic strategies in the postoperative setting of cardiac surgery. However, PAP may be misleading as it is dependent on cardiac output and requires accurate measurements. In the presence of residual lesions, analyses of some Doppler measurements may be misleading and not reflect real PAP. Should the TTE evaluation reveal non-conclusive, invasive hemodynamics remains the gold standard.